Acquiring English of Teaching Subject through CLIL in Teacher Training Bung Hatta University - Syofiani Jufri; Difiani Apriyanti (Politeknik Negeri Padang, 2019)
PGSD UBH (Pendidikan Guru Sekolah Dasar) is one of departments in Teacher Training Faculty under Bung Hatta University. The graduate students will be Elementary School teachers. The department provides curriculum which consists of subjects that needed by the candidate of Elementary School teachers, but unfortunately none involve English. Even, there is no English subject to be taught to the students. Meanwhile, as a teacher in this globalisation era, they must aware with all new information that grow rapidly from other countries, especially information about education, teaching, and their teaching subjects. Beside that, they also going to face pupils who are living in an era of advanced technology where information from all the world can be reached easily. There is no doubt that students of PGSD need to acquire English passively and actively. Therefore, CLIL (Content and Language Integrated Learning) training was conducted. CLIL was taught to 40 students of PGSD who were in semester two. By introducing the characteristics of CLIL, giving the direct model of CLIL, it was hoped the students have understood the base of CLIL. The students observed steps of CLIL that were shown by the model before giving their own performance. After giving a chance for each student to choose a topic that usually being taught to Elementary School pupils, they prepared themselves to teach the topic using CLIL. The result is the students considered much on their activating, language, and speaking. They focused more on the vocabularies and pronunciation. While the writing part was not dominan since the chosen topics were for low grades of elementary school.